RELASI MAYORITAS-MINORITAS UMAT BERAGAMA: PENGALAMAN MASYARAKAT TEGAL DALAM PENDIRIAN RUMAH IBADAH KONG MIAO: THE RELATIONSHIP BETWEEN MAJORITY-MINORITY RELIGIOUS PEOPLE: EXPERIENCE FROM TEGAL COMMUNITY IN THE ESTABLISHMENT OF THE HOUSE OF WORSHIP KONG MIAO - Rosidin Rosidin (Penamas, 2015)
This research is motivated by the anxiety of the establishment of houses of worship, especially among minority peoples like Khonghucu Kong Miao Confucius, as happened in Tegal. The case study can be read on the Joint Ministerial Decree (PBM) of Ministry of Religious Affairs and the Ministry of Home Affairs No. 8 and 9, 2006. The results showed that the existence of these regulations has been implemented well in Tegal. It can be seen from the establishment of Kong Miao Confucius as a form of local community needs. There are some factors that encourage the establishment of Kong Miao, including people‘s maturity in religious attitude, which raise their awareness to build the religious harmony. In addition, there are coordination and good communication between the government and religious leaders, which play a significant role in the establishment of houses of worship, especially Kong Miao. Generally, people in Tegal welcome Kong Miao, it is proven by organizations such as NU, Muhammadiyah, Al-Ershad that do not mind of this establishment. Keywords: House of Worship, Kong Miao, Tegal city, the relationship among religious people Penelitian ini berangkat kegelisahan akademik tentang pendirian rumah ibadah, terutama kalangan minorotas—seperti umat Khonghucu dengan Kong Miao di tengah mayoritas sebagaimana yang terjadi di Kota Tegal. Case study tersebut dapat dibaca dari efektivitas Peraturan Bersama Menteri (PBM) Menteri Agama dan Menteri Dalam Negeri No. 8 dan 9 Tahun 2006. Hasil penelitian menunjukkan, bahwa keberadaan regulasi tersebut telah dijalankan dengan baik di Kota Tegal, dengan pendirian Kong Miao sebagai bentuk kebutuhan masyarakat Khonghucu setempat. Adapun beberapa faktor yang mendorong pendirian Kong Miao antara lain adanya sikap dan kedewasaan dalam beragama oleh masing-masing umat yang mendorong adanya kesadaran untuk membangun kerukunan umat beragama. Selain itu, adanya koordinasi dan komunikasi yang baik antara pihak pemerintah dengan tokoh agama juga mempunyai peran yang signifikan dalam pendirian rumah ibadah, terutama Kong Miao. Secara umum, masyarakat Kota Tegal menerima dengan baik keberadaan Kong Miao, terbukti dari ormas seperti NU, Muhammadiyah, Al-Irsyad tidak mempermasalahkan hal tersebut. Kata Kunci: Rumah Ibadah, Kong Miao, Kota Tegal, hubungan antar umat beragama.